Sustained clinical remission under infliximab/rituximab combination therapy in a patient with granulomatosis with polyangiitis - Valor-Méndez, Larissa; Kleyer, Arnd; Rech, Jürgen; Manger, Bernhard; Schett, Georg (Autoimmunity Highlights, 2021)
Background: Granulomatosis with polyangiitis (GPA) is a systemic autoimmune disease characterized by small and medium vessel vasculitis. The use of biological therapies such as rituximab and infliximab has improved the treatment of ocular manifestations in GPA. Case report: We report a case of a 45-year-old Caucasian male suffering with rhinitis, sinubronchitis and exophthalmos. These clinical findings, subsequent biopsy and MRI were consistent with positive anti-neutrophil cytoplasm antibody (ANCA)/proteinase-3 and he was diagnosed with GPA with orbital involvement. He was refractory to cyclophosphamide at stable doses of methotrexate and a therapy with rituximab was started. Eventually and because of family planning methotrexate was replaced by azathioprine. Symptoms worsened and MRI revealed an increase in the granulomatous lesion in the orbit. Therefore, we decided to add infliximab to the combination of azathioprine and rituximab, our patient achieved then a long-term response. During the 10 years of the combined treatment, no adverse effects or systemic involvement occurred. Conclusions: This case suggests that the individual use of a combination of rituximab and infliximab may be a promising strategy for the treatment in the long term of refractory orbital GPA.
CRIS-Team Scopus Importer:2021-03-19
Keywords: Combined therapy; Granulomatosis with polyangiitis (GPA); Infliximab; Rituximab